PROBLEM PELAYANAN KEPENDUDUKAN BAGI PENGANUT AGAMA MARAPU DI SUMBA BARAT, NUSA TENGGARA TIMUR: RESIDENT SERVICE ISSUES FOR THE ADHERENTS OF MARAPU FAITH IN WEST SUMBA, EAST NUSA TENGGARA - Rosidin Rosidin (Balai Penelitian dan Pengembangan Agama Jakarta, 2016)
This paper attempts to answer the question of what are the concept of religion served by the state according the public, service issues encountered and how the state responses to the handle the issues. Data were collected through interviews, observation and document analysis. The results of the study are; firstly, according to underserved communities, the concept of religion does not necessarily meet all elements required by the state as the recognize religion, such as God, Prophet, and Holly Book. However, it need to meet the most essential elements, namely the belief system in God Almighty, ritual system or religious practice, formal religious institutions, and the recognition of community by registering to the government agency. Secondly, services related problems for the local religious believers of Marapu is related to the resident administration that rooted in the formal existence of the Marapu faith itself, such as a marriage certificate, ID card, family card, educational services and worship establishment registration. Thirdly, local government has already responded and seek improvementfor the system and submit a proposal to the central government as the appropriate authority. Keywords: Resident services, local religion, Marapu faith, Sumba. Tulisan ini berupaya menjawab pertanyaan, bagaimana konsep agama yang dapat dilayani negara menurut masyarakat, problem pelayanan yang muncul dan bagaimana respon negara sebagai pelayan dalam mengatasinya? Pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumen. Hasil penelitian adalah: Pertama, menurut masyarakat, konsep agama yang terlayani oleh negara tidak harus memiliki unsur-unsur yang harus ada dalam sebuah agama-agama yang diakui oleh negara, seperti; Tuhan, Nabi, dan Kitab Suci. Akan tetapi, unsur- unsur terpenting, seperti; sistem kepercayaan terhadap Tuhan yang Maha Esa, memiliki sistem ritual atau praktik keagamaan, dan memiliki lembaga keagamaan yang formal, serta pengakuan masyarakat dengan cara mendaftarkannya ke lembaga pemerintah. Kedua, problem pelayanan yang muncul bagi penganut agama lokal Marapu terkait administrasi kependudukan yang bersumber pada keberadaan agama Marapu sendiri, seperti; akte perkawinan, KTP, KK, layanan pendidikan, dan pendirian rumah ibadah. Ketiga, pemerintah daerah sebagai pelayan masyarakat sudah merespon dan berupaya memperbaiki sistem dan menyampaikan usulan kepada pemerintah pusat sesuai kewenangannya. Kata Kunci: Pelayanan kependudukan, agama lokal, agama Marapu, Sumba.